Persepsi Mahasiswa Pendidikan Masyarakat Angkatan 2023 Terhadap Scientific Learning dalam Pemahaman Konseptual - Ajizah, Laisya Nur; Asya’bani, Ikhsan Amirulloh; Shidqiyah, Shafa Firda; Azizah, Farah; Ahman, Ahman; Hakim, Ibrahim Al (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the perceptions of the 2023 Community Education students towards the scientific learning approach in understanding scientific concepts in higher education. This study uses a quantitative descriptive method, with data obtained through an online questionnaire distributed to students who have participated in scientific-based learning. Data analysis is conducted descriptively on all research data. The results show that the majority of students gave positive responses to the stages of learning such as observing, questioning, reasoning, and communicating. They felt more confident, active, and motivated in attending lectures. The average highest score was found in the statements that emphasize the process of exploration and reinforcement of understanding through open discussions. These findings are supported by literature reviews that indicate that the scientific approach is effective in improving learning outcomes and forming critical and reflective thinking patterns. This research concludes that the scientific learning approach is not only relevant to apply in elementary and secondary schools but also has a significant impact on improving the quality of learning in higher education, especially in shaping active, independent, and participatory students.